Running Dictation to Develop Students’ Listening Comprehension Ability - Hariswan Putra Jaya; Nova Lingga Pitaloka; Alhenri Wijaya (Indonesian Research Journal in Education |IRJE|, 2020)
The aims of this research were to find out whether or not there was a significant improvement on students’ listening comprehension achievement after being taught by running dictation method and their perceptions on running dictation. The sample of this research was the second semester students of English Education Study Program at one state university in South Sumatera, Indonesia. The method of this study was experimental study with a one group pretest and posttest design. The data were collected by using listening comprehension prestest and posttest. T-test was used to analyze the data. The results showed that t-value was greater than t-table. It can be concluded that running dictation could improve students’ listening comprehension achievement. Some implications are also made for future research.